A 3-year application of different mycorrhiza-based plant biostimulants distinctively modulates photosynthetic performance, leaf metabolism, and fruit quality in grapes (Vitis vinifera L.) - Ganugi, Paola; Caffi, Tito; Gabrielli, Mario; Secomandi, Elena; Fiorini, Andrea; Zhang, Leilei; Bellotti, Gabriele; Puglisi, Edoardo; Fittipaldi, Monica Broussard; Asinari, Florencia; Tabaglio, Vincenzo; Trevisan, Marco; et al. (Frontiers in Plant Science, 2023)
The use of microbial biostimulants in agriculture is recognized as a sustainable approach to promote crop productivity and quality due to improved nutrient uptake, enhanced stress tolerance, and improved ability to cope with non-optimal environments. The present paper aimed to comparatively investigate the effect of seven different commercial mycorrhizal-based treatments in terms of yield, phytochemical components, and technological traits of Malvasia di Candia Aromatica grape (Vitis vinifera L.) plants. Metabolomic analysis and photosynthetic performance were first investigated in leaves to point out biochemical differences related to plant growth. Higher photosynthetic efficiency and better PSII functioning were found in biostimulant-treated vines, reflecting an overall decrease in photoinhibition compared to the untreated plants. Untargeted metabolomics followed by multivariate statistics highlighted a robust reprogramming of primary (lipids) and secondary (alkaloids and terpenoids) metabolites in treated plants. The analysis of berry yield and chemical components exhibited significant differences depending on the biostimulant product. Generally, berries obtained from treated plants displayed improved contents of polyphenols and sugars, while yield remained unchanged. These ha formattato: Inglese (Regno Unito) ha eliminato: Oenological quality 2 This is a provisional file, not the final typeset article results elucidated the significant role of microbial biostimulants in determining the quality of grape berries and eliciting biochemical changes in vines. ha eliminato: ¶ 86 Previous works have highlighted the positive impact of AMF on 87 overall plant performance, including agronomical traits and 88 biochemical processes (Ganugi et al., 2019; Qiu et al., 2020). The 89 application of AMF can mitigate ha formattato: Olandese ha formattato: Tipo di carattere: Corsivo ha formattato: Tipo di carattere: Corsivo ha formattato: Italiano ha formattato: Tipo di carattere: Corsivo